O PROFESSOR DA EDUCAÇÃO PROFISSIONAL: FORMAÇÃO E PRÁTICA PEDAGÓGICA - Gomes, Sabrina Rodero Ferreira (2010)
In Brazil, this studies was inserted in a Professional Education teacher s context, however is so far to be discussed on the academic field nowadays. Many teachers don t discuss about technical courses because they believe that this kind of course doesn t match on the education field. They believe that it s important to prepare somebody particularly to work with. Actually the point is, if we need a professional, we need a graduation then what is the Professor importance? Could we say that the Professor is a real professional or he s just someone who knows the techniques and scientific knowledge that teaches students how to tighten a screw? Or maybe he s a really creatively person with a good background in his career but in the classroom he is not able to teach well because he doesn t have methodology on teachlearning process? To understand a little bit more about this subject, this research will be made by interviewing some engineers, technology s professionals and managers graduated and no-graduated teachers acting in these areas. We will read an analysis about graduation s courses in Brazil, called Special Graduation Programs to Pedagogic Teachers related to some professionals who contributes with their experiences day by day.(AU)